Normative data of an academic self-efficacy scale in college students from Lima - Sergio Alexis Dominguez-Lara (Interacciones)
This paper synthesize the obtention of normative data of Academic Situations Specific Perceived Self-efficacy Scale (ASSPSE) from Lima. Were evaluated 883 college students (75.5% women) with aged between 16 and 56 years (M = 22.16). The confirmatory factor analysis performed shows an unidimensional structure, and reliability coefficients (α, ω y H) have high magnitude. The ASSPSE scores not has normal distribution, and the normative data were elaborated with percentiles. The results are discussed and practical guidelines are given for the use of the norms.